Visiting Norwich, a UNESCO City of literature - Hasan, Md. Mahmudul (2019)
The Writers’ Centre Norwich (WCN), the University of East Anglia and other bodies hold national and international literary festivals and events in the city all the year round. In 1970, thanks to the initiative of writer and academic Malcolm Bradbury (1932-2000), UEA became the first British university to introduce a Masters programme in Creative Writing whose graduates include many literary giants, such as, Rose Tremain (1943-), Ian McEwan (1948-) and the 2017 Nobel Prize winner Kazuo Ishiguro (1954-). Because of these and other literary significances, in 2012, UNESCO declared Norwich a “City of Literature” and it is by far one of 28 such cities worldwide.